2019
DOI: 10.1111/1365-2656.12933
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic biomarkers of climatic impacts on declining insect populations: A key role for decadal drought, thermal buffering and amplification effects and host plant dynamics

Abstract: Widespread population declines have been reported for diverse Mediterranean butterflies over the last three decades, and have been significantly associated with increased global change impacts. The specific landscape and climatic drivers of these declines remain uncertain for most declining species. Here, we analyse whether plastic phenotypic traits of a model butterfly species (Pieris napi) perform as reliable biomarkers of vulnerability to extreme temperature impacts in natural populations, showing contrasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…In our region, lowland populations of some species have been shown to be more vulnerable toward extreme climatic events (i.e. summer drought) (Carnicer et al ). We also found that vegetation encroachment was more important in warmer areas and so affects butterfly assemblages in typical Mediterranean habitats more severely.…”
Section: Discussionmentioning
confidence: 89%
“…In our region, lowland populations of some species have been shown to be more vulnerable toward extreme climatic events (i.e. summer drought) (Carnicer et al ). We also found that vegetation encroachment was more important in warmer areas and so affects butterfly assemblages in typical Mediterranean habitats more severely.…”
Section: Discussionmentioning
confidence: 89%
“…However, there is ample evidence that body size is positively associated with female fecundity and negatively associated with stress in several butterfly species (Carnicer et al, 2019;Johnson et al, 2014;Niitepõld, 2019), including Leptidea sp. (Friberg & Wiklund, 2009;Lukhtanov et al, 2018).…”
Section: Scoring Of Developmental Time and Size Of Adult F1mentioning
confidence: 99%
“…Climate warming has been suggested as a possible factor underlying these negative trends; recent work has revealed the major role of climate in the dynamics of Mediterranean butterflies and shown the negative impact of increasing temperatures and drought on certain species (e.g. Merrill et al ., 2007; Zografou et al ., 2014; Mills et al ., 2017; Herrando et al ., 2019; Carnicer et al ., 2019). Moreover, given its small surface area, its physical limits as an island and the absence of high mountain ranges, species on Menorca are limited in their capacity to modify their distributions in response to climate change, as occurs in other areas (e.g.…”
Section: Introductionmentioning
confidence: 99%